Quality of the operations of reduced soil tillage and coffee seedlings transplating - Silva, Rouverson Pereira da; Voltarelli, Murilo Aparecido; Cassia, Marcelo Tufaile; Vidal, Diego Onofre; Cavichioli, Fábio Alexandre (Coffee Science - ISSN 1984-3909, 2014)
Soil tillage done with quality and conservation techniques are essential for the development of the coffee crop, as well as mechanized transplanting seedlings. The objective of this study was to evaluate the operational quality of mechanized sets for the reduced soil tillage and mechanized transplanting of coffee seedlings through quality indicators, using statistical process control. This study was carried out in the municipality of Matão – SP, Brazil. Operational and quality assessment were reflected in a sampling grid of 48 points spaced at 7.0 mx 20.0 m, and evaluated the operation of reduced soil tillage and transplanting seedlings by means of speed, slippage and alignment error of machinery. All variables showed asymmetric probability distribution and proved unstable as to statistical process control. The quality of operations of reduced soil tillage and mechanized transplanting of coffee seedlings proved all committed to quality indicators, due to the instability detected by statistical process control. The operation reduced soil tillage and mechanized transplanting of coffee seedlings skating show values below the ideal.